Pharmacokinetics of Marbofloxacin following Intramuscular Administration in Rabbits - Mir, Asif Majeed; Kumar, Nitesh; Shrivastav, Arpita; Singh, Swatantra Kumar; Ranjan, Rajeev; Yadav, Alok; Shrivastava, Neeraj; Sheikh, Taiyabali Jamaluddin (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Pharmacokinetic study of marbofloxacin was carried out in healthy rabbits following intramuscular administrations for five days. Blood samples were collected on 1st and 5th day of marbofloxacin administration. Concentrations of the marbofloxacin in blood plasma were estimated by microbiological assay. Kinetic parameters were calculated by using one compartment open model. Apparently higher plasma concentrations of the drug appeared at all intervals from 2.5 min to 24 h on 5th day as compared to 1st day of marbofloxacin administration with significant differences at 10.0 min and 12 h only. The minimum therapeutic concentration (≥ 0.25 µg/mL) of marbofloxacin was maintained up to 12 h and all kinetic parameters differ non-significantly between 1st and 5th day of marbofloxacin administration. On the basis of present findings, a satisfactory dosage regimen of marbofloxacin @ 2.14 mg/kg body weight followed by 2.04 mg/kg body weight intramuscular route at 24 h intervals can be recommended to maintain the minimum therapeutic concentration (≥ 0.25 µg/mL) during the treatment of bacterial infections in rabbit.